2021
DOI: 10.2174/1570179417666201216162055
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of Quinoline Derivatives and their Potential Biological Activities

Abstract: : Heterocyclic compounds containing the quinoline ring play a significant role in organic synthesis and therapeutic chemistry. Polyfunctionalized quinolines have attracted the attention of many research groups, especially those who work on the drug discovery and development. These derivatives have been widely explored by the research biochemists and are reported to possess wide biological activities. This review focuses on the recent progress in the synthesis of heterocyclic compounds based-quinoline and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…With the optimized reaction conditions in hand, we investigated the scope of the transformation of the imidazothiazolotriazine derivative 1 (Scheme 2), since quinoline is a well-known pharmacophore fragment. 8 It was found that substituents, especially on the oxindole moiety of substrate 1 , dramatically affected the formation of the quinoline derivatives 3 . Target compounds 3a–c with 3-pentyl substituents at the nitrogen atom of the quinoline moiety were formed selectively in good to high yields.…”
Section: Resultsmentioning
confidence: 99%
“…With the optimized reaction conditions in hand, we investigated the scope of the transformation of the imidazothiazolotriazine derivative 1 (Scheme 2), since quinoline is a well-known pharmacophore fragment. 8 It was found that substituents, especially on the oxindole moiety of substrate 1 , dramatically affected the formation of the quinoline derivatives 3 . Target compounds 3a–c with 3-pentyl substituents at the nitrogen atom of the quinoline moiety were formed selectively in good to high yields.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, quinolones attracted our attention, because of their low cytotoxicity on Vero cells (CC50 > 200 µ M) compared to the other compounds isolated [4] and because of their easy access by synthesis [5,6], facilitating the preparation of various analogs. Furthermore, quinoline derivatives are compounds of choice because they are known to possess a wide range of biological properties including anti-leishmanial activities [7][8][9][10][11][12]. They are considered as privileged structures in drug development [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…13 C NMR (125 MHz, CDCl 3 , 25 [M+H] + 310.1802, found 310.1799. 1,1,3a,9-Tetramethyl-1,1a,1a1,2,3,3a,9,10b-octahydro-10H-4-oxa-9-azacyclobuta [7,1]indeno [5,6-a]naphthalen-10-one (12). To a solution of zanthosimuline 7 (50 mg, 0.16 mmol, 1 eq.)…”
Section: Procedures and Analytical Description Of Compoundsmentioning
confidence: 99%
“…3 Shiro and coworkers addressed the chemistry and biological activity of quinoline up to 2015, 1 while Dib and coworkers reviewed the recent works on the synthesis and biological potential of quinoline-based compound up to 2021. 23 Hence, there is a need to bridge the gap regarding these potent pharmacological compounds since then to date. Our present review also presents diverse methods for the synthesis of quinoline, which can pave the way for synthetic chemists to achieve various synthetic modifications to access a new series of quinoline motifs for novel drug design.…”
Section: Introductionmentioning
confidence: 99%